Effects of gamma irradiation on the mechanical and thermal properties of cyanate ester/benzoxazine resin. (December 2017) - Zegaoui, Abdeldjalil; Wang, An-ran; Qadeer Dayo, Abdul; Tian, Bo; Liu, Wen-bin; Wang, Jun; Liu, Yu-guang
Abstract: In this study, thermosetting resin blends composed of cyanate ester (CE) and benzoxazine (BOZ) were prepared and then subjected to gamma-ray irradiation with doses up to 1000 kGy from a cobalt-60 gamma irradiator. The objective of this present study was to experimentally assess the effect of γ-ray irradiation on the mechanical behaviour, chemical structure and thermal properties of the CE/BOZ resin blends by the bending test, dynamic mechanical analysis (DMA), scanning electron microscopy (SEM), Fourier Transform Infrared (FTIR) and thermogravimetric analysis (TGA). The results showed that at a low radiation dose (250 kGy), the flexural strength and modulus, thermal stability, storage modulus and glass transition temperature of the CE/BOZ resin gradually declined first, then sharply increased when the radiation dose increased to 500 kGy and finally slightly dropped at the end with a dose of 1000 kGy. The decrease in the aforementioned properties could be ascribed to the degradation process including the rupture of chemical bonds and scission of molecular chains of the CE/BOZ resin blends, which were confirmed by the FTIR and SEM. However, a significant improvement in the thermal and mechanical properties of the blend was found when the radiation dose increased to 500 kGy. Highlights: A cyanate ester/benzoxazine resin was prepared and irradiated by γ- rays irradiation. Irradiated samples were studied by means of bending test, DMA, SEM, FTIR and TGA. Exposure to the low and high radiation doses caused chain scission of the molecular chains. Remarkable improvements were obtained at 500 kGy in the E ' and T g .